Cardiovascular Drug Labeling: Do They Have Information on Necessary Precautions for Older People? - Lucas Oliveira Marques; Roberta Coutinho Vasconcelos; André Oliveira Baldoni; Ana Cristina Nogueira Rodrigues Pestana; Farah Maria Drumond Chequer (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To analyze the existence of information on drug labeling intended for health professionals on the precaution of cardiovascular drugs use in older people. METHODS: This is a documentary study, carried out with the analysis of data contained in drug labelings. The existence of information on precautions in the use of drugs for older people as described in the 2016 Brazilian Consensus on Potentially Inappropriate Drugs for Older People (Consenso Brasileiro de Medicamentos Potencialmente Inapropriados para Idosos de 2016). RESULTS: Of the 29 drugs belonging to the cardiovascular system group that should be avoided by older people and are available in Brazil, 15 are independent of the clinical condition. Of these fifteen, only three drugs (20%) have explicit information in accordance with the Consensus (methyldopa, digoxin, and spironolactone); two (13.33%) have missing explicit information; four (26.66%) have explicitly discordant information; and six drug labels (40%) were categorized as non-explicit information. Regarding drug precautions according to clinical condition, 14 drugs were included. Of these, 12 (85.71%) have equal contraindications of that of Consensus on their drug labels, however, non-explicit; and two (14.28%) contraindications are missing. CONCLUSION: Most drug labels lack information on the precautions for the use of drugs in older people.